Psychogenic overeating: problems of classification, diagnosis, approaches to psychotherapy (literature review) - T. A. Karavaeva; M. V. Fomicheva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
In the article, we analyze the diagnosis of psychogenic overeating (ICD-10), consider the problem of its diagnostic criteria, similarities and differences with the diagnosis of binge-eating disorder (DSM-V), which complicate the work of researchers. We are looking at the need to differentiate the different types of binge eating disorder. The role of psychogenic overeating is noted as a pathogenetic factor that triggers the process of gaining excess weight. We describe in detail the biological (gender and hereditary predisposition), psychological (individual psychological personality traits, adaptive and compensatory resources) and sociocultural (style of family education, social ideas about the reference body image, features of communicative behavior, etc.) groups of factors involved in the formation of psychogenic overeating. The article emphasizes the role of psychological triggers of the disease associated with the emotional-volitional sphere, the specificity of reactions to stressful influences, psychological defenses and perception of the image of one’s body. The article also raises the problem of the lack of adapted and standardized psychodiagnostic tools aimed at studying psychogenic overeating, which complicates the formulation of an accurate diagnosis and the choice of methods of its treatment. The article also discusses such therapeutic approaches to the treatment of the described nosology, such as psychoanalysis, positive psychotherapy, gestalt therapy, transactional analysis, body-oriented therapy. Particular attention is paid to the cognitive-behavioral approach, which has shown high efficiency when working with patients with eating disorders. It is noted, that it is promising to develop algorithms for diagnostics and therapy of the described nosology, the feasibility of identifying individual targets of psychotherapeutic interventions to create personalized complex programs that increase the effectiveness of therapy in relation to immediate and long-term results.